1996
DOI: 10.1016/0014-5793(96)00860-5
|View full text |Cite
|
Sign up to set email alerts
|

Site‐specific cleavage reaction catalyzed by leadzyme is enhanced by combined effect of lead and rare earth ions

Abstract: Lead-dependent ribozyme (leadzyme) is a ribozyme working with Pb z+. In this paper, we have investigated the combined effect of metal ions, especially rare earth ions, on the cleavage reaction by the leadzyme. As a result, it was observed that although only a rare earth ion or another divalent ion except Pb z+ did not play a role as the catalyst, the addition of a rare earth ion in the presence of Pb z+ increased significantly the yield of the cleavage reaction. The result suggests that the complex between the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
45
0

Year Published

1998
1998
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(45 citation statements)
references
References 23 publications
0
45
0
Order By: Relevance
“…Firstly, the Pb 2 + -phos- [59,60] as well as Pb 2 + -dependent DNAzymes, [61] that is, RNA or DNA oligonucleotides with a structural motif that selectively binds Pb 2 + to promote hydrolytic cleavage of a second nucleic acid, could be selected by conducting in vitro selection experiments. Our results also explain why some leadzymes are strongly inhibited [62][63][64][65] by the presence of Mg 2 + and other divalent ions; such ions inhibit chelate formation of Pb 2 + . A difference in RNA binding between Pb 2 + and Mg 2 + has also been observed in hydrolytic cleavage experiments of a group II intron ribozyme [15] and other large RNAs.…”
Section: Discussionmentioning
confidence: 62%
“…Firstly, the Pb 2 + -phos- [59,60] as well as Pb 2 + -dependent DNAzymes, [61] that is, RNA or DNA oligonucleotides with a structural motif that selectively binds Pb 2 + to promote hydrolytic cleavage of a second nucleic acid, could be selected by conducting in vitro selection experiments. Our results also explain why some leadzymes are strongly inhibited [62][63][64][65] by the presence of Mg 2 + and other divalent ions; such ions inhibit chelate formation of Pb 2 + . A difference in RNA binding between Pb 2 + and Mg 2 + has also been observed in hydrolytic cleavage experiments of a group II intron ribozyme [15] and other large RNAs.…”
Section: Discussionmentioning
confidence: 62%
“…The total kinetics of combined 6-mers are in agreement with the buildup of 24-mer and the decay of the 30-mer ( Figure 1C). It is not clear, however, whether the same or a different bound Pb 2+ ion is involved in the two separate steps (3,4,8,10,21,22).The designed constructs showed a range of cleavage activity (Table S3 and Figure S3, Supporting Information), demonstrating various degrees of the influence of the functional group mutations that are highly context dependent. In particular, the P25 construct, where A25 is replaced by P, cleaves 3-fold (4 ( 0.1 min -1 ) faster than the WT.…”
mentioning
confidence: 94%
“…18,19 Sugimoto and Ohmichi found that lanthanides in general can accelerates the enzyme rate, although Pb 2+ is still required for activity. Among the 11 lanthanides they tested, Nd 3+ produced the highest rate enhancement.…”
mentioning
confidence: 99%